Different Candida parapsilosis clinical isolates and lipase deficient strain trigger an altered cellular immune response - Tóth, Renáta; Alonso, Maria F.; Bain, Judith M.; Vágvölgyi, Csaba; Erwig, Lars-Peter; Gácser, Attila (Frontiers in Microbiology, 2015)
Numerous human diseases can be associated with fungal infections either as potential causative agents or as a result of changed immune status due to a primary disease. Fungal infections caused by Candida species can vary from mild to severe dependent upon the site of infection, length of exposure and past medical history. Patients with impaired immune status are at increased risk for chronic fungal infections. Recent epidemiologic studies have revealed the increasing incidence of candidiasis caused by non-albicans species such as C. parapsilosis. Due to its increasing relevance we chose two distinct C. parapsilosis strains, to describe the cellular innate immune response towards this species. In the first section of our study we compared the interaction of CLIB 214 and GA1 cells with murine and human macrophages. Both strains are commonly used to investigate C. parapsilosis virulence properties. CLIB 214 is a rapidly pseudohyphae-forming strain and GA1 is an isolate that mainly exists in a yeast form. Our results showed, that the phagocyte response was similar in terms of overall uptake, however differences were observed in macrophage migration and engulfment of fungal cells. As C. parapsilosis releases extracellular lipases in order to promote host invasion we further investigated the role of these secreted components during the distinct stages of the phagocytic process. Using a secreted lipase deficient mutant strain and the parental strain GA1 individually and simultaneously, we confirmed that fungal secreted lipases influence the fungi’s virulence by detecting altered innate cellular responses. In this study we report that two isolates of a single species can trigger markedly distinct host responses and that lipase secretion plays a role on the cellular level of host pathogen interactions.